Minimal and robust clinically important difference of three fatigue measures in chronic stroke survivors. Issue 5 (4th July 2023) - Cheraghifard, Moslem; Sarlak, Nazanin; Taghizadeh, Ghorban; Azad, Akram; Fallah, Soheila; Akbarfahimi, Malahat
ABSTRACT: Background: Fatigue assessment scale (FAS), fatigue subscale of the Profile of Mood States (POMS-F), and vitality subscale of the Short Form Health Survey (SF-36-VT) are among the first and most widely used adapted tools for assessing post-stroke fatigue. Objective: To identify the minimal clinically important difference (MCID) and robust clinically important difference (RCID) of FAS, POMS-F, and SF-36-VT in stroke survivors. Methods: Participants completed the FAS, POMS-F, and SF-36-VT before and after receiving 6-week intervention including graded activity training and pacing therapy. MCID was calculated using the distribution-based and anchor-based methods. Further, accuracy, sensitivity, and specificity of calculated values using the distribution-based method were used for determining RCID. Result: A total of 124 stroke survivors participated in this study. MCID for FAS, POMS-F, and SF-36-VT was found to be 4.86, 3.32, and −10.10 (using score change) and 3.5, 2.5, and −10.5 (using ROC analysis), respectively. Using the distribution-based method, the MCID value obtained for the FAS was in the range of 3.16 to 8.76, for the POMS-F was in the range of 1.49 to 5.63, and for the SF-36-VT was in the range of −15.43 to −5.58. ½SD for FAS, ½ SD and 1.96 SEM for POMS-F, and 1.96 SEM and SD for SF-36-VT showed the best discriminative ability to use as the RCID. Conclusions: The MCID and RCID were calculated for FAS, POMS-F, and SF-36-VT using different methods. The results can be used by researchers and clinicians for interpreting their findings in subjects similar to those who participated in this study.